2022
DOI: 10.3389/fneur.2022.853417
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Degrees of Intraventricular Hemorrhage on Mortality and Neurological Outcomes in Very Preterm Infants: A Prospective Cohort Study

Abstract: ObjectiveIntraventricular hemorrhage (IVH) is a common complication in preterm infants and is related to neurodevelopmental outcomes. Infants with severe IVH are at higher risk of adverse neurological outcomes and death, but the effect of low-grade IVH remains controversial. The purpose of this study was to evaluate the impact of different degrees of IVH on mortality and neurodevelopmental outcomes in very preterm infants.MethodsPreterm infants with a gestational age of <30 weeks admitted to neonatal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
1
14
0
1
Order By: Relevance
“…The same outcome concerns grade III-IV of haemorrhage and other lesions noted on ultrasound including periventricular leukomalacia, porencephaly and ventriculomegaly [12]. On the other hand, Yong Wang's study indicated that preterm infants of <30 weeks' gestational age with I-II grade of haemorrhage had similar neurological outcomes and mortality compared to those without intraventricular haemorrhage, while III-IV grade was associated with cerebral palsy, disability and death at 18-24 months of corrected age [13].…”
Section: Classification Of Findings and Its Correlation With Prognosismentioning
confidence: 89%
“…The same outcome concerns grade III-IV of haemorrhage and other lesions noted on ultrasound including periventricular leukomalacia, porencephaly and ventriculomegaly [12]. On the other hand, Yong Wang's study indicated that preterm infants of <30 weeks' gestational age with I-II grade of haemorrhage had similar neurological outcomes and mortality compared to those without intraventricular haemorrhage, while III-IV grade was associated with cerebral palsy, disability and death at 18-24 months of corrected age [13].…”
Section: Classification Of Findings and Its Correlation With Prognosismentioning
confidence: 89%
“…In contrast, several studies suggest that mild IVH is not an independent factor for adverse neurodevelopmental outcomes [ 8 , 9 ]. Variations in the reported outcomes between our study and those reported in the literature could be attributed to a number of factors, including a single-center study, the type of study population (including infants with a higher GA who are at a lower risk of IVH), and sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The grading of IVH is used by clinicians to predict neurodevelopmental outcomes and to counsel families; however, there is no consensus in the literature regarding the impact of grades I–II IVHs and neurodevelopmental outcomes [ 3 , 5 , 6 ]. Some studies suggest that grades I–II IVHs are benign and have outcomes comparable to those with normal head ultrasound findings [ 7 , 8 , 9 ]. On the other hand, there are several studies that have reported adverse outcomes with these “minor” hemorrhages [ 5 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a brain insult is defined as perinatal asphyxia, which may occur with or without resuscitation and with or without hypoxic-ischemic encephalopathy. Regarding the severity of IVH, using the Papile classification, grades III and IV are classified as severe [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%